Analisis Penerapan JKN Mobile bagi Pengguna Lansia di Rumah Sakit Harapan dan Doa (RSHD) Kota Bengkulu - Krisda Vanitri Purba; Adityo Pratikno Ramadhan; Anita Marianata (University of Muhammadiyah Malang, 2024)
The JKN Mobile application has purposed to facilitate BPJS Health participants in employing JKN-KIS services without the need to come directly to the BPJS office. The aim of this research is to determine how JKN Mobile is employed by senior citizens at Bengkulu City's Harapan and Doa Hospitals, as well as to outline the services provided to JKN Mobile senior citizens at RSHD Bengkulu City.The research method employed in this study is the qualitative research method. Data collections were carried out through observation, interviews, and documentation. Informant selection technique using accidental sampling. The stages of data analysis used are data reduction, data presentation, and conclusion drawing. The results of this study indicate the application of JKN Mobile for older people users at Harapan and Doa Hospital, Bengkulu City, found problems with older people users who claimed to be quite difficult in using the JKN Mobile application to get services at the hospital such as not having a smartphone that supports it, not understanding how to use the JKN Mobile application, to difficulties due to not having a family companion as a source of information supporting the older people.